Związki intymne jako autorskie projekty życia – próba konceptualizacji ponowoczesnych wzorców relacji - Kuryś-Szyncel, Karolina; Jankowiak, Barbara (Wydawnictwo Naukowe UAM, 2015)
Today’s reality requires an individual to respond creatively to the challenges of the changing world and a liquid reality. Nonconformism and individualism are socially promoted. Still, many people want to live in an intimate relationship with a person close to them. There are visible changes of the individual life and anticipations about intimate relationships. Modern studies describe a lot of alternatives to the heterosexual marriage. The test results relating to the formal structure of compounds in the vast majority show no difference in the quality and durability of various forms of relationships. There is no in-depth analysis of the informal of relationship’s structure. In this article, it was assumed that an intimate relationship is a kind of life project through which people struggle with post-modern social reality. Via intimate relationships, partners can enhance personal creative potential and more creatively confront the events of life and face the challenges posed by developmental and life tasks. The theoretical analyses indicate the need to examine contemporary patterns of relationships. Perhaps those patterns will provide adequate socialization patterns. It was assumed that the relationship pattern includes: characteristics of partners, characteristic of the features of the formal and informal structure.
Intimate Relationships as Personal Life Projects – an Attempt to Conceptualize Post-modern Relationship Patterns
Keywords: intimate relationships; project of life; subjectivity; relations patterns